Unmet needs in outcome measures of Psoriatic Arthritis: focus on axial radiographic and nail involvement. - Lubrano di Scorpaniello, Ennio; Spadaro, Antonio (Acta Biomedica Atenei Parmensis, 2013)
Objectives: This article reviews some unmet needs on the outcome measures in Psoriatic Arthritis (PsA). In particular, the radiological assessment of axial PsA and the assessment of nail involvement still remain problematic and this, in turn, could affect the best management. At present, the radiological assessment of spine has been evaluated by using scoring systems borrowed from Ankylosing Spondylitis (AS). In particular, the Bath Ankylosing Spondylitis Radiology Index (BASRI) and the modified Stoke Ankylosing Spondylitis Spine Score (m-SASSS) have been validated for the axial PsA and a new index for assessing the radiological axial involvement in PsA was also developed, called Psoriatic Arthritis Spondylitis Radiology Index (PASRI). Nail involvement has been evaluated by two different instruments: the Nail Psoriasis Severity Index (NAPSI) and its modified version (mNAPSI). Both are good instruments but only a few data are available on these instruments when adopted at a daily clinical practice level.